Chto_jedim_v_tajge - Kovylin; Maksimova; Filchenko; Mulina; Kuznetsova
The languages of the collection, Eastern Khanty and Southern Selkup, (i) are severely endangered: each numbers under 20 last proficient speakers; (ii) have existing legacy data in Tomsk with limited access, which is to be improved as a result of the project; (iii) are characterized by areal contact contiguity; (iv) are ethnographically consistent, with the last traditional culture practitioners. The cooperative proposal between the University of Zurich and Tomsk State Pedagogical University builds on extended research experience with the respective languages, and relevant documentation methodology. The proposal pursues documentation and analysis of two endangered languages of Western Siberia, Russia in order to gain insight into local processes of area formation. born in Kuleevo - lower Tym river, moved to Napas after WWII, had 2 brother who died. Speaks Russian badly.